Multidrug resistant Enterobacteriaceae in New Zealand: a current perspective. Issue 2 (4th March 2017) - Toombs-Ruane, LJ; Benschop, J; Burgess, S; Priest, P; Murdoch, DR; French, NP
Abstract: In this article we review mechanisms and potential transmission pathways of multidrug resistance in Enterobacteriaceae, with an emphasis on extended-spectrum β-lactamase (ESBL)-production. This provides background to better understand challenges presented by this important group of antimicrobial resistant bacteria, and inform measures aimed at prevention and control of antimicrobial resistance in general. Humans and animals interact at various levels; household pets cohabit with humans, and other animals interact with people through direct contact, as well as through the food chain and the environment. These interactions offer opportunity for bacteria such as ESBL-producers to be shared and transmitted between species and, in turn, increase the risk of zoonotic and reverse-zoonotic disease transmission. A key step in curtailing antimicrobial resistance is improved stewardship of antimicrobials, including surveillance of their use, better infection-control and prevention, and a better understanding of prescribing practice in both veterinary and medical professions in New Zealand. This will also require prospective observational studies to examine risk factors for antimicrobial resistance. Due to the interconnectedness of humans, animals and the environment actions to effect the changes required should be undertaken using a One Health approach.